TNF receptors 1 and 2 exert distinct region‐specific effects on striatal and hippocampal grey matter volumes (VBM) in healthy adults. (4th October 2016) - Stacey, D.; Redlich, R.; Büschel, A.; Opel, N.; Grotegerd, D.; Zaremba, D.; Dohm, K.; Bürger, C.; Meinert, S. L.; Förster, K.; Repple, J.; Kaufmann, C.; et al.
Abstract : Tumour necrosis factor alpha (TNFα) has been implicated in the pathophysiology of neurodegenerative and neuropsychiatric disease, with research highlighting a role for TNFα in hippocampal and striatal regulation. TNFα signals are primarily transduced by TNF receptors 1 and 2 (TNFR1 and TNFR2), encoded by TNFRSF1A and TNFRSF1B, which exert opposing effects on cell survival (TNFR1, neurodegenerative; TNFR2, neuroprotective). We therefore sought to explore the respective roles of TNFR1 and TNFR2 in the regulation of hippocampal and striatal morphology in an imaging genetics study. Voxel‐based morphometry was used to analyse the associations between TNFRSF1A (rs4149576 and rs4149577) and TNFRSF1B (rs1061624) genotypes and grey matter structure. The final samples comprised a total of 505 subjects (mean age = 33.29, SD = 11.55 years; 285 females and 220 males) for morphometric analyses of rs1061624 and rs4149576, and 493 subjects for rs4149577 (mean age = 33.20, SD = 11.56 years; 281 females and 212 males). Analyses of TNFRSF1A single nucleotide polymorphisms (SNPs) rs4149576 and rs4149577 showed highly significant genotypic associations with striatal volume but not the hippocampus. Specifically, for rs4149576, G homozygotes were associated with reduced caudate nucleus volumes relative to A homozygotes and heterozygotes, whereas for rs4149577, reduced caudate volumes were observed in C homozygotes relative to T homozygotes and heterozygotes. Analysis of the TNFRSF1B SNP rs1061624 yielded a significant association with hippocampal but not with striatal volume, whereby G homozygotes were associated with increased volumes relative to A homozygotes and heterozygotes. Our findings indicate a role for TNFR1 in regulating striatal but not hippocampal morphology, as well as a complementary role for TNFR2 in hippocampal but not in striatal morphology. Abstract : The findings of this study indicate a role for tumour necrosis factor receptor (TNFR) 1 in regulating striatal but not hippocampal morphology, as well as a complementary role for TNFR2 in hippocampal but not in striatal morphology.